Predictive value of the neutrophil-to-lymphocyte ratio in patients with deep neck space infection secondary to acute bacterial tonsillitis - BİNNETOĞLU, ADEM; YUMUŞAKHUYLU, ALİ CEMAL (ELSEVIER IRELAND LTD, 2015)
Objective: The aim of this study was to determine whether the neutrophil-to-lymphocyte ratio (NLR) can be used as a predictor for deep neck space infections (DNSIs) that occur as a complication of acute bacterial tonsillitis in the pediatric population. Materials and methods: We evaluated the NLR values of 180 pediatric patients diagnosed with acute bacterial tonsillitis with or without DNSI who presented to the Otolaryngology Department of Marmara University Hospital between 2010 and 2013. In cases in which DNSI was suspected, the patients underwent complete otolaryngological examination and radiological imaging including CT and MRI. NLR was calculated in all the subjects and was compared between the patients with acute bacterial tonsillitis without DNSI and those with DNSI. Results: With regard to the tonsillitis-related complications, 17 patients had peritonsillar abscess (9.4%); five, parapharyngeal abscess (2.8%); and two, retropharyngeal abscess (1.1%). The mean NLR was significantly higher in the patients of acute bacterial tonsillitis with DNSI (P < 0.05). The optimum cut-off value of NLR was determined to be 5.4. Conclusion: This study is the first to investigate the relationship between NLR and DNSI as a complication of acute bacterial tonsillitis. The results demonstrated that the NLR value could be a potential laboratory parameter for diagnosing DNSIs. (C) 2015 Elsevier Ireland Ltd. All rights reserved.
Keywords: Neutrophil-to-lymphocyte ratio; Inflammation; Acute bacterial tonsillitis; Deep neck infection; ASSOCIATION; ABSCESSES